Urban Sufism: The Dynamic of Cosmopolitan Religious Community - Jaenuri Jaenuri (Teosofia: Indonesian Journal of Islamic Mysticism, 2022)
The phenomenon of urban Sufism represents the new form of Sufism in the modern era. However, the diversity in urban society shows the dynamic of Sufism. This article is a qualitative study based on a library investigation that applies the Sufistic approach. Data collection was carried out by examining sources related to urban Sufism. This article found that internal and external factors influence the formation of religiosity in urban society. By nature, human beings need spirituality to seek their essence. In contrast, the external factors are discourses of modernisation and globalisation which are increasingly strengthened by some factors such as self-alienation, spiritual dryness, loss of humanism, hedonism, and materialism. The type of religiosity needed by modern urban society is universal, humane, social, logical, inclusive, and based on love and the principle of freedom.Contribution: This study contributes to providing a new horizon of religious reconstruction, especially for urban communities that need a more open and inclusive model of religiosity.